The Program for the Improvement of Primary Care Access and Quality (PMAQ) in Brazil-interview with James Macinko - Macinko, James; da Cunha Saddi, Fabiana (Sociedade e Cultura, 2018)
James Macinko is a Professor and researcher in public health policy and health systems research and equity, with extensive experience in primary care throughout the world, including the Brazilian Family Health Strategy. He is currently Professor of Health Policy and Management and Community Health Sciences at the UCLA Fielding School of Public Health. He previously held positions as Associate Professor of Public Health and Health Policy at New York University and former director of the NYU MPH program. He was a Robert Wood Johnson Foundation Health and Society Scholar at the University of Pennsylvania from 2006 to 2008 and a Fulbright Scholar in Brazil in 2002. He has worked and still works on several collaborative projects with Brazilian public health researchers and has been involved in both formal and informal consultations with the Department of Basic Care at the Brazilian Ministry of Health (DAB/MoH). This includes his participation in an international seminar on the PMAQ organized by the DAB/MoH and official support to lead the edition of JACM’s supplementary number on PMAQ, published in 2017.